ANALYSIS OF MATHEMATICAL DISPOSITION IN ELEMENTARY SCHOOLS MATHEMATICS LEARNING - Yeni Fitriya; Rika Wulandari; Conny Dian Sumadi (Jurnal Cakrawala Pendas, 2023)
Mathematical dispositions play an important role in mathematics learning. Students who have a negative disposition will have an impact on their learning. Aspects of mathematical disposition consist of self-confidence, perseverance, learning with full responsibility, never giving up, and having an interest in challenging, reflective, and creative problems. Given the importance of the mathematical disposition aspect, it should be of particular concern in learning. This study aims to provide a description of the mathematical dispositions of students in grades 4, 5, and 6 at SDN Banyuajuh 1. Using a qualitative case study approach, this research was conducted to obtain in-depth results. The researcher is the main instrument and is supported by several supporting instruments, such as a mathematical disposition questionnaire, observation sheets, interview guidelines, and documentation guidelines. The findings in this study indicate that the condition of the high school students' mathematical dispositions is in a good category. This is indicated by several aspects of achievement, such as the implementation of mathematics and the positive level of student self-confidence. However, not all aspects of mathematical disposition can be achieved properly. Aspects of flexibility, monitoring ability, and student reflection abilities need to be improved. Not only that but teachers also need to pay attention to aspects of cultural appreciation and integration in mathematics. Students' mathematical dispositions are not only influenced by teacher factors but also by student factors. Learning environment factors also play an important role. So, this study provides implications and recommendations for mathematics learning activities that are oriented toward students' mathematical dispositions. Disposisi matematis memiliki peran penting dalam pembelajaran matematika. Siswa yang memiliki disposisi negatif akan berdampak pada kegagalan belajar. Aspek disposisi matematis yang terdiri dari percaya diri, tekun, belajar dengan penuh tanggungjawab, pantang menyerah, memiliki ketertarikan terhadap soal yang menantang, reflektif dan kreatif. Mengingat pentingnya aspek disposisi matematis, seharusnya menjadi perhatian khusus dalam pembelajaran. Penelitian ini bertujuan untuk memberikan deskripsi terhadap kondisi disposisi matematis siswa kelas 4, 5 dan 6 di SDN Banyuajuh 1. Melalui pendekatan kualitatif metode studi kasus, penelitian ini dilakukan guna memperoleh hasil yang mendalam. Peneliti sebagai instrumen utama dan didukung beberapa instrumen pendukung seperti angket disposisi matematis, lembar observasi, pedoman wawancara dan pedoman dokumentasi. Temuan dalam penelitian ini menunjukan bahwa kondisi disposisi matematis siswa kelas tinggi dalam kategori baik. Hal ini terindikasi dari beberapa aspek capaian seperti implementasi matematika hingga tingkat kepercayaan diri siswa yang positif. Namun, tidak semua aspek disposisi matematis dapat terrcapai dengan baik. Aspek fleksibiltas, kemampuan monitoring dan kemampuan refleksi siswa perlu ditingkatkan. Bukan hanya itu, guru juga perlu memperhatikan aspek apresiasi dan integrasi budaya dalam matematika. Disposisi matematis siswa tidak dipengaruhi oleh faktor guru saja, melainkan faktor dari siswa, faktor lingkungan belajar juga berperan penting. Jadi, penelitian ini memberi implikasi dan rekomendasi pada kegiatan pembelajaran matematika yang berorientasi pada disposisi matematis siswa.